Investigation on glass-forming ability, Flexural strength and microwave dielectric properties of Al2O3-doped LMZBS glasses. Issue 8 (1st June 2019) - Qin, Tianying; Zhong, Chaowei; Yang, Hongcheng; Qin, Yang; Zhang, Shuren
Abstract: In this work, a new high flexural strength microwave dielectric material for LTCC applications, (1-x) Li2 OMgOZnOB2 O3 SiO2 -xAl2 O3 (x = 1–10 wt %) (LMZBSA) glass-ceramics, was prepared by conventional solid-state reaction method. The effects of Al2 O3 -doped Li2OMgOZnOB2 O3 SiO2 (LMZBS) glass on its glass-forming ability (GFA) and activation energy were investigated by Dietzel, Saad-Paulin methods and Kissinger model, respectively. Comparing the undoped sample with the 10 wt % of Al2 O3 -doped LMZBS glass the parameters of ΔT and S which characterize the GFA increase by 35% and twice, respectively. Meanwhile, the addition of Al2 O3 will reduce the activation energy, making initial crystallization easier. And then the impact of Al2 O3 on the phase composition, flexural strength and microwave dielectric properties of LMZBSA glass-ceramics was studied systematically. It shows that the content of Al2 O3 has a great influence on the flexural strength of LMZBSA glass-ceramics, and different composition is responsible for its microwave dielectric properties. LMZBSA glass-ceramics with 5 wt % Al2 O3 sintered 2 h at 900 °C showed the highest relative density (96.41%) and flexural strength (σ = 190 MPa), optimum microwave dielectric properties ( ε r  = 6.8, Q × f  = 12500 GHz, τ f  = −45 ppm/°C).